Complications following total wrist replacement: A single-center retrospective review - Cyrus Tsun-Kit Lau; Raymond Chung-Wai Wan; Wai-Wang Chau; Michael Chu-Kay Mak; Wing-Lim Tse; Pak-Cheong Ho (Journal of Orthopaedics, Trauma and Rehabilitation)
Background/Purpose: Total wrist replacement (TWR) is an alternative to wrist fusion in advance wrist arthritis with the advantage of preserving the wrist motion. TWR is, however, infrequently performed in Asia-Pacific region. This study aimed to describe our institution's experience in managing complications following TWR. Methods: This study represents a single-center retrospective review of all patients who underwent TWR at the Department of Orthopedics and Traumatology, Prince of Wales Hospital in Hong Kong. The study period spans from 1 January 2004 to 1 March 2023. Recorded demographic parameters include gender, age upon surgery, pathology, types of implants, and follow-up period. Outcomes focused particularly on postoperative complications and need for revision surgery. Results: Twelve TWR from 10 Chinese-Asian patients were reviewed with a mean follow-up duration of 97.4 months. The incidence of complications in our study was as follows: loosening (16.67%), metallosis (8.3%), infection (8.3%), and stiffness (8.3%). One patient required conversion to total wrist arthrodesis due to metallosis and stiffness. Conclusion: TWR offers promising solutions for managing painful arthritic wrists. However, it's crucial to recognize that complications can arise, necessitating further surgical intervention. Surgeons must thoroughly comprehend these risks to provide informed counseling to patients and explore alternative treatment approaches.